Construction and evaluation for 15-word lists based on the Deese-Roediger-McDermott paradigm - Hong, Patricia; Mattos Pimenta Parente, Maria Alice de; Erna Claessens, Peter Maurice; Galduróz, Ruth Ferreira [UNESP] (FapUNIFESP (SciELO), 2020)
Based on studies conducted in accordance with the Deese-Roediger-McDermott (DRM) paradigm, in which words of a list tend to evoke other related items, used in false memory research, this study produced 15 lists of semantically related words for Brazilian Portuguese. For the preparation of the lists, certain criteria were considered, such as word length and frequency of words in a Brazilian Portuguese corpus. Pre-selection guided by linguistic characteristics aimed to control possible biases among volunteers. Semantic association and concreteness tests were carried out to determine the suitability of the selected items, and a free recall test was performed to evaluate evocation characteristics. We suggest using word lists in researches that evaluate false memories.
Keywords: Deese-Roediger-McDermott paradigm; False memories; Related words